2020
DOI: 10.1002/cam4.3060
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle associated factors and risk of urinary bladder cancer: A prospective cohort study from Norway

Abstract: A number of lifestyle associated factors, such as high body mass index (BMI), low physical activity, and related metabolic disorders, are associated with increased risk of cancer at several sites. For urinary bladder cancer (BC), such studies show inconsistent results, which could result from inadequate adjustment for smoking and occupational exposure. In the population-based Janus Cohort (n = 292 851), we investigated the independent and combined impact of BMI, physical activity, blood pressure, and blood lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…For instance high BMI is associated with low 25(OH) D concentrations, and have in some studies showed a tendency to be inversely related to BC risk. 7,36 In our analysis, when stratifying by BMI; a reduced BC risk for deficient 25(OH)D concentrations was only seen in the category of BMI ≥25.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…For instance high BMI is associated with low 25(OH) D concentrations, and have in some studies showed a tendency to be inversely related to BC risk. 7,36 In our analysis, when stratifying by BMI; a reduced BC risk for deficient 25(OH)D concentrations was only seen in the category of BMI ≥25.…”
mentioning
confidence: 58%
“…Occupational working titles were categorized as high risk (yes or no) and was based on existing knowledge about chemical exposures in certain occupations that previously has shown to be related to BC risk. 7,29,30 More details about the categorization of high risk occupations are published previously. 7 Education was categorized as unknown, compulsory, upper secondary and college/university.…”
Section: Covariatesmentioning
confidence: 99%
See 2 more Smart Citations
“…An awareness of the benefits of of PA appears encourage people to have healthy lifestyle habits [17,30]. Indeed, the more frequently people engage in PA, better their lifestyle habits will be acquired.…”
Section: Summary Of Findingsmentioning
confidence: 99%